EFFORTS TO IMPROVE TEACHER COMPETENCE IN COMPILING SYLLABUS AND RPP THROUGH WORKSHOPS AT SD NEGERI 15 PARIAMAN RAILWAYS - Ratna Juwita (LPPM Ekasakti University, 2022)
The subject of the research is the teacher of SD Negeri 15 Jalan Kereta Api . Research procedure with two cycles. Each cycle consists of two workshops in which each cycle contains planning, action, observation, and reflection. Data collection techniques with observation, documentation. Data analysis carried out in this study is reduction, data presentation and conclusion drawing. The results of the study revealed that there was an increase in teachers in making learning devices in each cycle. The results of this study indicate that the implementation of the workshop can improve the ability of teachers in compiling syllabus and lesson plans as well as increasing the number of teachers in compiling these tools. What is expected to be achieved.